Strengthening the Policy of the Healthy Living Community Movement (GERMAS) "Building a Healthy Living Culture for a Golden Indonesia" - Bambang Setiaji; Etik Retno Wiyati; Ira Octaviana M; Susi Annisa Uswatun Hasanah; Leny Wulandari (Eduvest - Journal of Universal Studies, 2025)
Healthy Living Community Movement (GERMAS) is a strategic initiative launched by the government to improve the quality of public health through changes in healthier lifestyles. However, the implementation of GERMAS still faces various challenges, such as low public awareness, lack of sustainable policy support, and limited coordination between stakeholders. This study aims to analyze the effectiveness of the GERMAS policy in encouraging healthy living behavior in the community. This study uses a qualitative research method. The data collection technique in this study is through literature studies. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The results of the study show that during the seven years of Germas implementation, the burden of non-communicable diseases in Indonesia is still high, influenced by various risk factors and unhealthy lifestyles that are less supportive. The burden of financing catastrophic diseases in Indonesia, in 2022, reached IDR 24.1 trillion, up 34.3% from the previous year. This shows that the Germas policy has not been effective in reducing the burden of health costs. This condition risks increasing the burden of financing in the health sector, threatening economic stability, and hampering efforts to achieve Golden Indonesia. The suggested alternatives are (1) Strengthening the Germas policy to increase stakeholder compliance, (2) Establishing success indicators that bind across sectors, (3) Encouraging Germas promotion and education.